Long-Range Three-Dimensional Tracking of Nanoparticles Using Interferometric Scattering Microscopy - Kasaian, Kiarash; Mazaheri, Mahdi; Sandoghdar, Vahid (ACS nano, 2024)
Tracking nanoparticle movement is highly desirable in many scientific areas, and various imaging methods have been employed to achieve this goal. Interferometric scattering (iSCAT) microscopy has been particularly successful in combining very high spatial and temporal resolution for tracking small nanoparticles in all three dimensions. However, previous works have been limited to an axial range of only a few hundred nanometers. Here, we present a robust and efficient measurement and analysis strategy for three-dimensional tracking of nanoparticles at high speed and with nanometer precision. After discussing the principle of our approach using synthetic data, we showcase the performance of the method by tracking gold nanoparticles with diameters ranging from 10 to 80 nm in water, demonstrating an axial tracking range from 4 μm for the smallest particles up to over 30 μm for the larger ones. We point out the limitations and robustness of our system across various noise levels and discuss its promise for applications in cell biology and material science, where the three-dimensional motion of nanoparticles in complex media is of interest.
CRIS-Team Scopus Importer:2024-11-01
Keywords: diffusion; interferometric scattering microscopy (iSCAT); interferometry; single-particle tracking (SPT); three-dimensional tracking